Explanatory hypotheses of the ecology of new clinical presentations of Dissociative Identity Disorders in youth - Gauld, Christophe; Espi, Pauline; Revol, Olivier; Fourneret, Pierre (Frontiers in Psychiatry, 2022)
Dissociative Identity Disorders (DIDs) are controversial psychiatric conditions encountered in clinical practice and nosology. DID as described in the international classifications has little similarity with the clinical picture of “DID” met in current youth psychiatry. From this Perspective, we hypothesize that this current clinical presentation does not satisfy the categorical criteria of the international classifications. Based on the two terminological challenges related to the definition of DID (i.e., the notion of dissociative disorders and the different meanings of the term identity), we propose to differentiate two distinct entities from each other. The first is medical and listed in diagnostic criteria of international classifications; the second comes from popular culture and refers to the vast majority of clinical presentations received in daily clinical practice—presented under the term Dissociative Identity Conditions (DIC). Since the status of DIC is a hot topic in current clinical psychiatry, we aim to identify eight possible explanations that can be provided to support its occurrence: (1) impact of iatrogenicity; (2) factors of suggestibility and desire for social acceptability; (3) psychoanalytic explanations; (4) neuropsychological explanations; (5) socio-cognitive explanations; (6) emotional labeling; (7) narrative explanations; (8) and transient illnesses explanations. In conclusion, we sustain that DIC results from a narrative interpretation of medical discourse by popular culture, developing in patients presenting undeniable distress. Such a transient disease fits in an ecological niche, which echoes the values of society, persisting under the action of a need for narrative continuity of the self.